2016
DOI: 10.1128/jb.00995-15
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissection of the CroRS Two-Component System Required for Resistance to Cell Wall Stressors in Enterococcus faecalis

Abstract: Bacteria use two-component signal transduction systems (TCSs) to sense and respond to environmental changes via a conserved phosphorelay between a sensor histidine kinase and its cognate response regulator. The opportunistic pathogen Enterococcus faecalis utilizes a TCS comprised of the histidine kinase CroS and the response regulator CroR to mediate resistance to cell wall stresses such as cephalosporin antibiotics, but the molecular details by which CroRS promotes cephalosporin resistance have not been eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(91 citation statements)
references
References 52 publications
5
85
0
Order By: Relevance
“…As noted above, previous studies indicate that CroRS Efs modulates gene expression in response to stress from cell wall-targeting antibiotics (12,26), and the functional conservation identified here suggests this is also the case with CroRS Efm . Hence, we hypothesize that CroRS Efm enhances expression of genes that are important for resistance upon sensing cell wall stress.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…As noted above, previous studies indicate that CroRS Efs modulates gene expression in response to stress from cell wall-targeting antibiotics (12,26), and the functional conservation identified here suggests this is also the case with CroRS Efm . Hence, we hypothesize that CroRS Efm enhances expression of genes that are important for resistance upon sensing cell wall stress.…”
Section: Discussionsupporting
confidence: 77%
“…We previously identified a second TCS (CisRS), found in a subset of E. faecalis strains, that is capable of influencing the activity of CroRS Efs under certain conditions due to mutual overlap in the identity of so-called "specificity" residues of the CroS and CisS kinases that dictate response regulator specificity for TCS kinases (26)(27)(28). However, extensive studies indicated that "cross talk" between CisS and CroR Efs only occurs in the absence of CroS Efs and is not physiologically relevant (26).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations